Comparative study of two incentive schemes in Malaysian paddy production - Yunus-Junaid, Busayo Rashidat; Ismail, Mohd Mansor; Mohd Nawi, Nolila (Kementerian Pendidikan Malaysia, 2013)
Domestic rice production has occupied the minds of policy makers and this explains the reason for the establishment of granary areas, where irrigation schemes established by the Malaysian government expected to enhance productivity of rice farming along with improved technologies. The improved infrastructures and technologies were to increase the self sufficiency level but unfortunately the country still imports cheaper rice from abroad. The overriding objective of this paper was to analyze the comparative advantage of paddy production in selected granary areas and to examine the government policies by taking a look at the impacts of the government incentive schemes and comparing the change(s) brought about by these schemes in two different years. In 2006, incentives given to the farmers included paddy fertilizer, paddy production incentive and petrol subsidies only while the new scheme launched in 2008 includes additional fertilizer, pesticide, plowing, and yield increase incentives. Two of the indicators of comparative advantage, the Domestic Resource Cost and the Social Cost Benefit were used to calculate the comparative advantage of paddy. The results indicate that the comparative advantage of paddy production in 2007 is lower than that of 2009. This shows that the new incentive scheme has helped to increase paddy production, and hence farmers income, particularly at a period when the country was battling with the global food crisis.